2017
DOI: 10.1080/1059924x.2017.1356777
|View full text |Cite
|
Sign up to set email alerts
|

A case history introducing the oregon ag seminar series - keys to program and research-to-practice success

Abstract: This case history of Oregon state’s Ag Seminar Series is consistent with the Socio-Ecological Model, demonstrating how policy at a state level can influence an organizational approach with impacts that ultimately influence safety practices on the farm. From modest beginnings, the Ag Seminar Series, offered through a workers compensation insurance company, now serves over 2,300 Oregon farmers annually in English and Spanish. This case offers unique but also replicable methods for educators, insurers, and resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Initiatives from governmental state agencies have been shown to improve the health of agricultural workers, and it was demonstrated that the development of interagency agreements may strengthen programs and injury surveillance. 14,15 There was an acknowledged need to support comprehensive programs that strengthen relationships via networking, sharing information, appropriate legislation, and enhancing leadership, as well as developing best practices in safety management practices. 16,17 To be good stewards of resources, the already created safety curricula need to be promoted nationally and be available for free download shared by multiple agencies, schools, and institutions.…”
Section: Breadth Of the Socio-ecological Modelmentioning
confidence: 99%
“…Initiatives from governmental state agencies have been shown to improve the health of agricultural workers, and it was demonstrated that the development of interagency agreements may strengthen programs and injury surveillance. 14,15 There was an acknowledged need to support comprehensive programs that strengthen relationships via networking, sharing information, appropriate legislation, and enhancing leadership, as well as developing best practices in safety management practices. 16,17 To be good stewards of resources, the already created safety curricula need to be promoted nationally and be available for free download shared by multiple agencies, schools, and institutions.…”
Section: Breadth Of the Socio-ecological Modelmentioning
confidence: 99%